A study of the emotional labor of the professional librarians and the support staff of the University of the Philippines Diliman Library - Cruz, Roscelle C. (2014)
Emotional labor occurs when an employee alters his or her behavior to show appropriate conduct in order to conform to the display rules of an organization required to complete a job. This study focuses on the emotional labor of the librarians and support staff of the University of the Philippines Diliman Library, consisting of the Main Library and the libraries of the 22 degree-granting Units. The study concentrated on the identification of individual factors that impact the emotional labor of the target population. This study was able to determine how the librarians and support staff of UPD Library carry out emotional labor, as well as how they cope with the positive and negative effects of such.